1990
DOI: 10.1002/jmor.1052030106
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the fine structure of the endocrine dorsal body cells of Helisoma duryi (mollusca) induced by mating

Abstract: The morphology and the organization of the endocrine dorsal bodies (DB) of non-reproducing virgin and castrated, and reproducing mated Helisoma duryi have been examined using serial sectioning. The DB cells occur in two masses on the mid-dorsal side of the cerebral commissure, each of which has a cortical zone containing the cell bodies and a medulla where cell processes terminate. The cell bodies measure 10-15 μm in diameter, and are arranged in lobules of 6-12 cells. The complex cell processes are winding an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1990
1990
2009
2009

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…The lateral lobes of the brain of Lymnaea and Helisoma are known to have an inhibitory effect on growth, but a stimulatory effect on reproduction (Roubos et al 1980;Saleuddin and Kunigelis 1984). Recently, a close association between the DB and the CDC has been suggested in Helisoma (Khan et al 1990). It is likely that the above endocrine centres function in an integrated manner.…”
Section: Fig 12mentioning
confidence: 91%
“…The lateral lobes of the brain of Lymnaea and Helisoma are known to have an inhibitory effect on growth, but a stimulatory effect on reproduction (Roubos et al 1980;Saleuddin and Kunigelis 1984). Recently, a close association between the DB and the CDC has been suggested in Helisoma (Khan et al 1990). It is likely that the above endocrine centres function in an integrated manner.…”
Section: Fig 12mentioning
confidence: 91%
“…Cells of the dorsal bodies are organized in groups on both sides of the perineurium of the cerebral ganglia allowing for direct innervation by neurosecretory cells of these ganglia (Saleuddin et al 1997;Saleuddin and Ashton 1996). Physiological characteristics of dorsal bodies suggest that these glands are inactive in virgin snails, are activated by mating, and remain active during the reproductive phase of the organisms (Joosse and Geraerts 1983;Khan et al 1990;Saleuddin et al 1997). Ultrastructural analyses have suggested that the juxtaganglionar organ of prosobranch snails may be analogous to the dorsal bodies (Switzer-Dunlap 1987).…”
Section: Hormonal Control Of Sexual Differentiation and Reproduction mentioning
confidence: 97%
“…In Helix aspersa, the direct stimulation of organites implicated in the albumen gland secretion by the gonad was demonstrated using an ultrastructural study of organ associations cultured on a semi-solid medium (Gomot and Courtot, 1979 In H aspersa, egg laying is generally preceded by multiple mating as it is reported in other species (Van Duivenboden and Ter Maat, 1985;Baur, 1988;Khan et al, 1990). Several data demonstrated the importance of mating as a stimulant of the female sexual activity as compared to virgin snails (Van Duivenboden, 1983;Saleuddin etal, 1983Saleuddin etal, , 1989Khan et al, 1990; Saleuddin et al,…”
Section: Introductionmentioning
confidence: 94%
“…Several data demonstrated the importance of mating as a stimulant of the female sexual activity as compared to virgin snails (Van Duivenboden, 1983;Saleuddin etal, 1983Saleuddin etal, , 1989Khan et al, 1990; Saleuddin et al,…”
Section: Introductionmentioning
confidence: 99%